Analysis of Obstacles in the Implementation of Online Learning for Undergraduate Students of Electrical Engineering - Muhammad Ikhsan Kurniawan; Oriza Candra (Universitas Negeri Padang, 2021)
The Department of Electrical Engineering, especially the S1 (Education) study program, has carried out an online learning process in the even semester of the 2019-2020 academic year as an option to make the learning process continue during the COVID-19 outbreak. This study aims to analyze the obstacles experienced by undergraduate students in Electrical Engineering, Faculty of Engineering, State University of Padang in the implementation of the online learning process. The type of research used is descriptive qualitative research. Data retrieval was carried out by distributing a googleform link in which there were 14 statements and distributed to 77 students of the 2017-2020 undergraduate study program. In this study, the results obtained indicate that the most significant obstacle experienced by students in the implementation of online learning is the lack of good delivery of material by lecturers. The online learning process really needs to be optimized and also needs to be evaluated to improve the implementation of online learning in the future.